2019
DOI: 10.26873/svr-766-2019
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Chronic Heat Stress in Broilers by Dietary Supplementation of Novel Feed Additive Combinations

Abstract: Heat stress causes economic losses via decreasing feed intake, nutrient digestion, weight gain, feed conversion, immunity, carcass quality and increasing mortality in broilers. The aim of the study was to assess the ability of dietary additive combinations to ameliorate the detrimental effect caused by chronic heat stress (32 ± 2ºC for 24 h per d) on performance, carcass traits, metabolic status and economic efficiency of broiler chickens. A total of 420, one-day old Cobb-500 broiler chicks were assigned into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
3
7
0
1
Order By: Relevance
“…Water intake was not significantly altered by the interaction among broiler strain × heat stress × boldo treatments with an increase in water consumption by heat-stressed birds of both strains. Our results are consistent with those of previous studies [30][31][32]. The adverse effect of HS on broiler growth performance can be attributed to the mucosal epithelial damage caused by HS that impairs nutrients absorption.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Water intake was not significantly altered by the interaction among broiler strain × heat stress × boldo treatments with an increase in water consumption by heat-stressed birds of both strains. Our results are consistent with those of previous studies [30][31][32]. The adverse effect of HS on broiler growth performance can be attributed to the mucosal epithelial damage caused by HS that impairs nutrients absorption.…”
Section: Discussionsupporting
confidence: 93%
“…Previous investigations attributed the alterations in profitability in broiler production to the variations in growth rate and the cost of one-day-old chicks, drugs, labor, feed, veterinary services, and the sale price of birds [75,76]. Our results are consistent with those reported in earlier studies [32,77,78].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ibrahim et al, observed that total blood lipid was significantly lowered in dietary Cr supplemented 14 . Al-Sultan et al reported Cr supplementation increased the serum concentration of calcium, phosphorous, and potassium and decreased the level of sodium 15 . Amatya et al found that Cu, Zn, Fe, and Mn retention was better when Cr was supplemented in the feed of broilers 16 .…”
Section: Introductionmentioning
confidence: 99%